The End of Days : African American Religion and Politics in the Age of Emancipation - Harper, Matthew (Book collections on Project MUSE., 2016)
For four million slaves, emancipation was a liberation and resurrection story of biblical proportion, both the clearest example of God's intervention in human history and a sign of the end of days. Matthew Harper demonstrates how black southerners' theology, in particular their understanding of the end times, influenced nearly every economic and political decision they made in the aftermath of emancipation.